Transparency in the public debt of the municipality of Hermosillo, Sonora - Morales Tostado, María del Carmen (Posgrados de la División de Ciencias Económica Administrativas, 2022)
The objective of this work, is to approach the topic of transparency, giving emphasis compliance whith obligations. For this, the reports of the transparency index and fiscal availability of the municipalities whit the largest number of inhabitants in the State of Sonora are considered, focusing mainly on analyzing the municipality of Hermosillo in a pediod of 10 years from 2010 to 2020. It is undeniable that the pandemic forced a rethinking of government work and generated a troublesome that is still present in society, due to the urgent need to allocate resurces for extraordinary expenses in the health sector. Also, the pandemic negatively impacted the economy in general, causing the closure of 486 companies and the financial lethargy of the State. Fort the topic to be investigated, the qualitative appoach was chosen, describing the legal framework of transparency and financial discipline, reviewing some books and articles that deal whit the topic, and the electronic pages of the municipalities were also reviewed. Among the results, the following can be shared, according to data from the SHCP in 2020 Hermosillo is the third most indebted municipality in the country.